2000
DOI: 10.1097/00007632-200012010-00011
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Disc Degeneration and Facet Joint Osteoarthritis on the Segmental Flexibility of the Lumbar Spine

Abstract: Axial rotational motion was most affected by disc degeneration, and the effects of disc degeneration on the motion were similar between genders. Facet joint osteoarthritis also affected segmental motion, and the influence differed for male and female spines. Further studies are needed to clarify whether the degenerative process of facet joint osteoarthritis differs between genders and how facet joint osteoarthritis affects the stability of the spinal motion segment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
359
5
16

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 522 publications
(416 citation statements)
references
References 47 publications
24
359
5
16
Order By: Relevance
“…The motion restriction obtained with the UC affected all three planes, even though this reduction failed to achieve significance in lateral bending and axial rotation. This finding, not observed with the Wallis, is of great interest since Fujiwara et al showed that axial rotation was most affected by disc degeneration, leading to increased ROM with mild and intermediate degeneration [27]. No significant additional motion was observed with either of the implants at the adjacent segments, suggesting a possibly reduced risk of ASD compared to fusion.…”
Section: Discussionmentioning
confidence: 77%
“…The motion restriction obtained with the UC affected all three planes, even though this reduction failed to achieve significance in lateral bending and axial rotation. This finding, not observed with the Wallis, is of great interest since Fujiwara et al showed that axial rotation was most affected by disc degeneration, leading to increased ROM with mild and intermediate degeneration [27]. No significant additional motion was observed with either of the implants at the adjacent segments, suggesting a possibly reduced risk of ASD compared to fusion.…”
Section: Discussionmentioning
confidence: 77%
“…Fujiwara et al [8] found that changes in the ROM due to segmental degeneration differs in the three main motion planes. They found axial rotation to be mostly affected by degeneration and reported an increase in motion due to degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Another important cause of axial back pain is facet joint osteoarthritis, which consists in the decrease of the thickness and regularity of the cartilage layer of the facet joints, also called apophyseal or zygoapophysial joints. Disc degeneration and facet joint osteoarthritis are commonly observed together in the same patient and spinal level [20,26,35] and a possible correlation between these two pathologies is currently debated [62].…”
Section: Discogenic Painmentioning
confidence: 99%